2017
DOI: 10.1155/2017/1678584
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Inflammation-Based Prognostic Scores in a Cohort of Patients with Resectable Esophageal Cancer

Abstract: Background A number of studies have revealed that inflammation-based prognostic scores, such as Glasgow prognostic score (GPS), modified Glasgow prognostic score (mGPS), and C-reactive protein and albumin ratio (C/A ratio), are associated with poor outcome in cancer patients. However, until now, no study has investigated the role of these prognostic scores in a cohort of neoadjuvant-treated esophageal adenocarcinomas (nEAC) and squamous cell carcinomas (nESCC). Methods Patients had laboratory measurements with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 63 publications
1
8
1
Order By: Relevance
“…As previous studies, the patients who were classified into the group of score 2 were limited (only 1 case in this study) 19 , 20 . Xiao-li Wei et al, Xiao-ling Xu et al and G. Jomrich et al had reported that high GPS (1-2) was not significantly associated with shorter OS in non-selected or resectable ESCC patients, but, multivariate analysis identified that GPS (0/1-2) was the independent prognostic factor for 10-year OS among stage T1N0 ESCC in our study 20 - 22 , which was in accordance with the result from N. Hirahara et al among elderly ESCC patients (age≥70 years) 19 . In 2007, the first study in colon and rectal cancer from McMillan DC et al indicated that the modified GPS (mGPS) was significantly associated with overall survival 23 .…”
Section: Discussioncontrasting
confidence: 52%
“…As previous studies, the patients who were classified into the group of score 2 were limited (only 1 case in this study) 19 , 20 . Xiao-li Wei et al, Xiao-ling Xu et al and G. Jomrich et al had reported that high GPS (1-2) was not significantly associated with shorter OS in non-selected or resectable ESCC patients, but, multivariate analysis identified that GPS (0/1-2) was the independent prognostic factor for 10-year OS among stage T1N0 ESCC in our study 20 - 22 , which was in accordance with the result from N. Hirahara et al among elderly ESCC patients (age≥70 years) 19 . In 2007, the first study in colon and rectal cancer from McMillan DC et al indicated that the modified GPS (mGPS) was significantly associated with overall survival 23 .…”
Section: Discussioncontrasting
confidence: 52%
“…[4][5][6] The major prognostic impact of inflammatory markers can be ascribed to a cytokine-driven immunogenic tumor microenvironment and a significant prognostic role of inflammation-based biomarkers and scores has recently been shown in a number of malignant diseases. 5,7,[26][27][28] One of the newly emerging prognostic scores is the SII, based on platelets, neutrophils, and lymphocytes. As a combination of both NLR and PLR, SII firstly has been confirmed as superior prognostic factor in hepatocellular carcinoma and then in small cell lung cancer reflecting patient's inflammatory status.…”
Section: Discussionmentioning
confidence: 99%
“…This data goes in good accordance with our recently published data, that shows, that albumin and CRP based prognostic scores have to be used carefully in EC patients. Nevertheless, in the subgroup of neoadjuvantly treated AEG patients, we found the mGPS to be a prognostic marker [ 27 ]. Therefore, we evaluated the mGPS in a cohort neoadjuvantly treated AEG patients in this underlying study.…”
Section: Discussionmentioning
confidence: 99%